Trail paper poetry - Pelham, David (New York Little Simon/Simon & Schuster Children's Publishing, 2007)
Follow the silvery trail through an enchanting maze of stunning pop-up landscapes that range from tranquil to mysterious to magical.
Cover title.
Keywords: Maze puzzles -- Juvenile literature; Landscapes -- Poetry; Pop-up books -- Specimens